# 1. Factor the following: a. 25ab-10ax - 20b + 8x             b. by - 4by - ax + 4abc.ax^2 + 2x^3 + a + 2x

Asked on by genieee

hala718 | High School Teacher | (Level 1) Educator Emeritus

Posted on

a. 25ab-10ax - 20b + 8x

First we will rearrange terms.

25ab - 20b + 8x - 10ax

Now we will factor 5b from the first 2 terms.

==> 5b(5a-4) + 8x - 10ax

Now we will factor -2x from the last two terms.

==> 5b(5a-4) -2x( -4 + 5a)

==> 5b(5a-4) - 2x( 5a-4).

Now we will factor (5a-4).

==> (5a-4)( 5b -2x).

c.ax^2 + 2x^3 + a + 2x

First we will factor x^2 from the first two terms.

==> x^2( a+ 2x) + ( a+ 2x)

Now we will factor ( a+ 2x).

==> (a+2x) ( x^2 +1)

neela | High School Teacher | (Level 3) Valedictorian

Posted on

To factor

a.

25ab-10ax - 20b + 8x

=5a(5b-2x) -4(5b-2x)

25ab-10ax - 20b + 8x = (5b-2x)(5a-4)

b.

by-4by-ax+4ab  could be simplied to -3by -a(x+b) but not factored.

c.

ax^2 + 2x^3 + a + 2x = x^2(a+2x) +1(a+2x).

ax^2 + 2x^3 + a + 2x =  (a+2x)(x^2+1)

We’ve answered 317,754 questions. We can answer yours, too.